2001
DOI: 10.3184/030823401103169874
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Pyridine Derivatives from Malononitrile with Bisarylidenecycloalkanone under Microwave Irradiation

Abstract: Six pyridine derivatives were synthesised by one-step reaction of malononitrile with 2,5-bisarylidenecyclopentanones or 2,6-bisarylidenecyclohexanones in methanol / sodium hydroxide under microwave irradiation in 75~92% yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…One procedure for the synthesis of pyridine derivatives is from the reactions of unsaturated ketones with active methylene compounds. 66 The reactions might proceed through a Michael addition reaction, followed by a cyclization reaction. Amr et al 67 reported a versatile and efficient procedure for the synthesis of pyridosteroids utilizing the reactivity of steroids with an unsaturated ketone core in their reactions with various reagents.…”
Section: Synthesis Of Pyridines Fused To Steroidal Skeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…One procedure for the synthesis of pyridine derivatives is from the reactions of unsaturated ketones with active methylene compounds. 66 The reactions might proceed through a Michael addition reaction, followed by a cyclization reaction. Amr et al 67 reported a versatile and efficient procedure for the synthesis of pyridosteroids utilizing the reactivity of steroids with an unsaturated ketone core in their reactions with various reagents.…”
Section: Synthesis Of Pyridines Fused To Steroidal Skeletonmentioning
confidence: 99%
“…One procedure for the synthesis of pyridine derivatives is from the reactions of unsaturated ketones with active methylene compounds. 66 The reactions might proceed through a Michael addition reaction, followed by a cyclization reaction. Amr et al 67 Moffat oxidation is a chemical reaction for the oxidation of primary and secondary alcohols to aldehydes and ketones, respectively.…”
Section: Synthesis From Acyclic αβ-Unsaturated Ketonesmentioning
confidence: 99%
“…The montmorillonite clay contains both acidic and basic sites, and behaves as a ditopic catalyst that allows for the direct formation of 292. The same synthetic strategy was employed to construct substituted 4 Η − pyran derivatives by condensation of α,β-unsaturated ketones with activated methylene compounds such as malononitrile [421].…”
Section: Pyranopyrimidinesmentioning
confidence: 99%
“… 17 The pyridine moiety is more attractive because of its widespread chemical applications. 18 , 19 For example, 3-cyanopyridine derivatives have many uses, such as IKKb inhibitors and A2A adenosine receptor antagonists. 20 Recently, several protocols have been reported to produce 3-cyanopyridine derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocyclic components containing nitrogen are seemingly the essential component in the structure of numerous novel designs and the synthesis of organic components and they naturally exist as alkaloid compounds, which are vital for use as medicinal drug compounds . The pyridine moiety is more attractive because of its widespread chemical applications. , For example, 3-cyanopyridine derivatives have many uses, such as IKKb inhibitors and A2A adenosine receptor antagonists . Recently, several protocols have been reported to produce 3-cyanopyridine derivatives.…”
Section: Introductionmentioning
confidence: 99%